Downregulation of p66Shc can reduce oxidative stress and apoptosis in oxidative stress model of marginal cells of stria vascularis in Sprague Dawley rats - Hao C; Wu X; Zhou R; Zhang H; Zhou Y; Wang X; Feng Y; Mei L; He C; Cai X; Wu L (Dove Medical Press, 2019)
Cong Hao,1–3 Xuewen Wu,1–3 Ruoyu Zhou,1–3 Hao Zhang,1,2 Yulai Zhou,1,2 Xinxing Wang,1,2 Yong Feng,1–3 Lingyun Mei,1–3 Chufeng He,1–3 Xinzhang Cai,1–3 Lisha Wu1–3 1Department of Otolaryngology Head and Neck Surgery, Xiangya Hospital Central South University, Changsha 410008, Hunan, People’s Republic of China; 2Hunan Province Key Laboratory of Otolaryngology Critical Diseases, Changsha 410008, Hunan, People’s Republic of China; 3National Clinical Research Center for Geriatric Disorders, Xiangya Hospital, Central South University, Changsha 410008, Hunan, People’s Republic of ChinaCorrespondence: Lisha WuDepartment of Otolaryngology Head and Neck Surgery, Xiangya Hospital Central South University, Changsha 410008, Hunan, People’s Republic of ChinaEmail ENTLisaWu@163.comBackground: p66Shc, a Src homologue and collagen homologue (Shc) adaptor protein, mediates oxidative stress signaling. The p66Shc-null mice have increased lifespan and enhanced resistance to oxidative stress. Studies have also indicated its potential role in inner ear aging, which can lead to deafness.Objective: The aim of this study was to determine the effects of p66Shc down-regulation on the marginal cells (MCs) of the inner ear stria vascularis.Methods: Primary MCs were isolated from neonatal rats and treated with glucose oxidase to induce oxidative stress. The cells were transduced with adenovirus expressing siRNA, and the knockdown was verified by Western blotting. The reactive oxygen species (ROS) levels and apoptosis were analyzed using the DCFH-DA probe and Annexin-V/7-AAD staining respectively. The ultrastructure of the differentially-treated cells was examined by transmission electron microscopy (TEM).Results: The in vitro oxidative stress model was established successfully in rat MCs. Knockdown of p66Shc alleviated the high ROS levels and apoptosis in the glucose oxidase-treated cells. In addition, glucose oxidase significantly increased the number of peroxisomes in the MCs, which was decreased by p66Shc inhibition.Conclusion: Oxidative stress increases p66Shc levels in the marginal cells of the inner ear, which aggravates ROS production and cellular injury. Blocking p66Shc expression can effectively reduce oxidative stress and protect the MCs.Keywords: p66Shc, marginal cells of stria vascularis, oxidative stress, peroxisome